At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Alright, let's solve the problem step-by-step in detail.
We are given the recursive formula:
[tex]\[ a_n = \left(a_{n-1}\right)^2 - a_{n-1} \][/tex]
and we know that:
[tex]\[ a_4 = 870 \][/tex]
Our task is to find the first two terms of this sequence.
1. Start by figuring out [tex]\( a_3 \)[/tex]:
[tex]\[ a_4 = \left(a_3\right)^2 - a_3 \][/tex]
[tex]\[ 870 = \left(a_3\right)^2 - a_3 \][/tex]
This is a quadratic equation in [tex]\( a_3 \)[/tex]:
[tex]\[ \left(a_3\right)^2 - a_3 - 870 = 0 \][/tex]
Solve this quadratic equation using the quadratic formula:
[tex]\[ a_3 = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where [tex]\( a = 1 \)[/tex], [tex]\( b = -1 \)[/tex], and [tex]\( c = -870 \)[/tex]:
[tex]\[ a_3 = \frac{1 \pm \sqrt{1 + 4 \cdot 870}}{2} \][/tex]
[tex]\[ a_3 = \frac{1 \pm \sqrt{3481}}{2} \][/tex]
[tex]\[ a_3 = \frac{1 \pm 59}{2} \][/tex]
[tex]\[ a_3 = 30 \text{ or } a_3 = -29 \][/tex]
Since we are working with whole numbers, we discard the negative value:
[tex]\[ a_3 = 30 \][/tex]
2. Next, find [tex]\( a_2 \)[/tex] using the same recursive formula:
[tex]\[ a_3 = \left(a_2\right)^2 - a_2 \][/tex]
[tex]\[ 30 = \left(a_2\right)^2 - a_2 \][/tex]
This is another quadratic equation in [tex]\( a_2 \)[/tex]:
[tex]\[ \left(a_2\right)^2 - a_2 - 30 = 0 \][/tex]
Solve this quadratic equation using the quadratic formula:
[tex]\[ a_2 = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where [tex]\( a = 1 \)[/tex], [tex]\( b = -1 \)[/tex], and [tex]\( c = -30 \)[/tex]:
[tex]\[ a_2 = \frac{1 \pm \sqrt{1 + 4 \cdot 30}}{2} \][/tex]
[tex]\[ a_2 = \frac{1 \pm \sqrt{121}}{2} \][/tex]
[tex]\[ a_2 = \frac{1 \pm 11}{2} \][/tex]
[tex]\[ a_2 = 6 \text{ or } a_2 = -5 \][/tex]
Since we are working with whole numbers, we discard the negative value:
[tex]\[ a_2 = 6 \][/tex]
3. Finally, find [tex]\( a_1 \)[/tex]:
[tex]\[ a_2 = \left(a_1\right)^2 - a_1 \][/tex]
[tex]\[ 6 = \left(a_1\right)^2 - a_1 \][/tex]
This is one more quadratic equation in [tex]\( a_1 \)[/tex]:
[tex]\[ \left(a_1\right)^2 - a_1 - 6 = 0 \][/tex]
Solve this quadratic equation using the quadratic formula:
[tex]\[ a_1 = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where [tex]\( a = 1 \)[/tex], [tex]\( b = -1 \)[/tex], and [tex]\( c = -6 \]: \[ a_1 = \frac{1 \pm \sqrt{1 + 4 \cdot 6}}{2} \] \[ a_1 = \frac{1 \pm \sqrt{25}}{2} \] \[ a_1 = \frac{1 \pm 5}{2} \] \[ a_1 = 3 \text{ or } a_1 = -2 \] Since we are working with whole numbers, we discard the negative value: \[ a_1 = 3 \] Therefore, the first two terms of the sequence are: \[ a_1 = 3 \] \[ a_2 = 6 \] The correct set of answers is \( \boxed{3, 6} \)[/tex].
We are given the recursive formula:
[tex]\[ a_n = \left(a_{n-1}\right)^2 - a_{n-1} \][/tex]
and we know that:
[tex]\[ a_4 = 870 \][/tex]
Our task is to find the first two terms of this sequence.
1. Start by figuring out [tex]\( a_3 \)[/tex]:
[tex]\[ a_4 = \left(a_3\right)^2 - a_3 \][/tex]
[tex]\[ 870 = \left(a_3\right)^2 - a_3 \][/tex]
This is a quadratic equation in [tex]\( a_3 \)[/tex]:
[tex]\[ \left(a_3\right)^2 - a_3 - 870 = 0 \][/tex]
Solve this quadratic equation using the quadratic formula:
[tex]\[ a_3 = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where [tex]\( a = 1 \)[/tex], [tex]\( b = -1 \)[/tex], and [tex]\( c = -870 \)[/tex]:
[tex]\[ a_3 = \frac{1 \pm \sqrt{1 + 4 \cdot 870}}{2} \][/tex]
[tex]\[ a_3 = \frac{1 \pm \sqrt{3481}}{2} \][/tex]
[tex]\[ a_3 = \frac{1 \pm 59}{2} \][/tex]
[tex]\[ a_3 = 30 \text{ or } a_3 = -29 \][/tex]
Since we are working with whole numbers, we discard the negative value:
[tex]\[ a_3 = 30 \][/tex]
2. Next, find [tex]\( a_2 \)[/tex] using the same recursive formula:
[tex]\[ a_3 = \left(a_2\right)^2 - a_2 \][/tex]
[tex]\[ 30 = \left(a_2\right)^2 - a_2 \][/tex]
This is another quadratic equation in [tex]\( a_2 \)[/tex]:
[tex]\[ \left(a_2\right)^2 - a_2 - 30 = 0 \][/tex]
Solve this quadratic equation using the quadratic formula:
[tex]\[ a_2 = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where [tex]\( a = 1 \)[/tex], [tex]\( b = -1 \)[/tex], and [tex]\( c = -30 \)[/tex]:
[tex]\[ a_2 = \frac{1 \pm \sqrt{1 + 4 \cdot 30}}{2} \][/tex]
[tex]\[ a_2 = \frac{1 \pm \sqrt{121}}{2} \][/tex]
[tex]\[ a_2 = \frac{1 \pm 11}{2} \][/tex]
[tex]\[ a_2 = 6 \text{ or } a_2 = -5 \][/tex]
Since we are working with whole numbers, we discard the negative value:
[tex]\[ a_2 = 6 \][/tex]
3. Finally, find [tex]\( a_1 \)[/tex]:
[tex]\[ a_2 = \left(a_1\right)^2 - a_1 \][/tex]
[tex]\[ 6 = \left(a_1\right)^2 - a_1 \][/tex]
This is one more quadratic equation in [tex]\( a_1 \)[/tex]:
[tex]\[ \left(a_1\right)^2 - a_1 - 6 = 0 \][/tex]
Solve this quadratic equation using the quadratic formula:
[tex]\[ a_1 = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where [tex]\( a = 1 \)[/tex], [tex]\( b = -1 \)[/tex], and [tex]\( c = -6 \]: \[ a_1 = \frac{1 \pm \sqrt{1 + 4 \cdot 6}}{2} \] \[ a_1 = \frac{1 \pm \sqrt{25}}{2} \] \[ a_1 = \frac{1 \pm 5}{2} \] \[ a_1 = 3 \text{ or } a_1 = -2 \] Since we are working with whole numbers, we discard the negative value: \[ a_1 = 3 \] Therefore, the first two terms of the sequence are: \[ a_1 = 3 \] \[ a_2 = 6 \] The correct set of answers is \( \boxed{3, 6} \)[/tex].
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.